Universal Intellectual Property Rights: Too Much of a Good Thing? - Emmanuelle Auriol; Sara Biancini; Rodrigo Paillacar (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper studies the incentives that developing countries have to protect intellectual properties rights (IPR). On the one hand, free-riding on rich countries technology reduces their investment cost in R&D. On the other hand, firm that violates IPR cannot legally export in a country that enforces them. Moreover free-riders cannot prevent others to copy their own innovation. The analysis predicts that the willingness to enforce IPR is U-shaped in a country GDP: small/poor countries are willing to respect IPR to access advanced economies markets, while large emerging countries are more reluctant to do so because technological transfers from the West boost their production capacity and their domestic markets. Universal enforcement of IPR yields a higher level of innovation and global welfare only if the developing country does not innovate. A partial enforcement of IPR, strict in the north and lax in the south, is socially better if the developing country invests enough in R&D and if its interior market is large. The theoretical predictions of the model are tested with the help of panel data. The empirical analysis supports the theoretical results.
Keywords: F12; F13; F15; L13; O31; O34; 330; intellectual property rights; innovation; imitation; oligopoly; trade policy; developing countries